Environmental management and sustainability: a case study in the agency of the Bank of Brazil Alagoa Nova/PB - Medeiros, Maria do Socorro Bezerra; Barbosa, Robson Fernandes; Sousa, Jackson Epaminondas de; Alexandre, Stefane Nogueira; Oliveira, Cláudio Germano dos Santos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In recent times, environmental management and sustainability are occupying an increasing space between society and business, which consequently leads to changes in political control, environmental management and monitoring of production processes of organizations. Thus this workhad the objective to show how agency employees Alagoa Nova / PB assess the environmental management and sustainable development in the Banco do Brasil as a tool for competitive advantage. The work focused on the fact that the financial sector is well advanced in environmental issues, seeking to integrate the exercise of their social practices of their business, highlighting the business strategy adopted by the Banco do Brasil, with regard to actions focused on Agenda 21 and the Eco-Efficiency Program. Thisis a case study and can be characterized as exploratory, where it was applied a structured questionnaire with the six employees that make up the agency under study. The results showed that the vision of environmental sustainability of the employees is paradoxical, therefore, not informed or aware and participate in environmental actions promoted by the bank and at the same time declared that these actions are very important to their customers as to their environments work